Prognosticators and Outcomes of Patients with Renal Cell Carcinoma and Adjacent Organ Invasion Treated with Radical Nephrectomy - Borregales, Leonardo D. (Urol Oncol, 2015)
OBJECTIVE: To study the natural history, prognosticators, and outcomes in patients with RCC with extension of tumor beyond Gerota’s fascia and/or invading contiguously into the adrenal gland (pT4). PATIENTS AND METHODS: From 1992 to 2012, we identified 61 patients who underwent radical nephrectomy and were found to have pT4 disease. Clinicopathological variables were queried using univariate analysis to identify relevant prognostic variables. Cox proportional hazards model was used for multivariate analysis of predictors of cancer-specific survival. Survival plots were estimated using Kaplan-Meier method and survival analysis using log-rank test. RESULTS: Median age was 56 years (IQR 49-64) and 49 (81.7%) had ECOG PS 0-1. At diagnosis, 22 (36.1%) patients were M0 and 39 (63.9%) were M1. Forty-nine(80.3%) patients had clear cell RCC. Twenty-four(39.3%) had sarcomatoid features. Thirty-nine(69.6%) patients had Fuhrman grade 3-4. There were twenty-six(42.6%) pN0 patients, 16(26.2%) pN1, and 19(31.1%) pNx. Median CSS was 37 months for M0 and 8 months for M1 patients. On multivariate analysis, preoperative LDH and alkaline phosphatase, M stage, pN stage, and sarcomatoid dedifferentiation were significantly associated with survival. CONCLUSIONS: Survival in patients with pT4 remains poor. pT4 is associated with a locally and regionally invasive biology that requires specific attention and warrants careful study. Understanding the drivers of this unique phenotype will generate therapeutic interventions that can change the behavior of these uniquely aggressive tumors.